Youth, Leisure and Home: Space, Place and Identity - Abbott-Chapman, Joan; Robertson, Margaret (Loisir et Société / Society and Leisure, 2001)
AbstractThis qualitative and quantitative research investigates the leisure activities of 265 young adolescents in Tasmania, Australia, in relation to their social constructs of home and neighbourhood as private and public spaces, and in the practical contexts of their day to day lives. As these young people search for meaning and identity in a fast changing world dominated by economic and technological globalisation, the symbolic materials available to them both socially and spatially are examined using innovative research methods which involve visual as well as verbal triggers. Findings show that their chosen activities, while reflecting global trends in the use of information and communication technology, focus mainly on friendship network building in the immediate locale and take place predominantly in home and neighbourhood. Favourite places for leisure pursuits also emphasise the importance and idealisation of the ’traditional’ home and of the natural environment in the search for private places in which to withdraw and reflect. Findings also suggest that the adolescents seek private spaces for safe seclusion or group activities with close friends as part of the process of construction of self as a reflexive and symbolic project. The inherently ’conservative’ and highly gendered responses of the sample are discussed in the context of current sociocultural theories linking space, place and identity.